2022
DOI: 10.1021/acscatal.2c00174
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Catalytic Sites for Highly Efficient Electrochemical Oxidation of the Aldehyde and Hydroxyl Groups in 5-Hydroxymethylfurfural

Abstract: 5-Hydroxymethylfurfural oxidation reaction (HMFOR) is regarded as a promising approach to attain biomassderived high-value chemical products. As the HMFOR process is complicated, and the two-step oxidation of the aldehyde group and hydroxyl group in 5-hydroxymethylfurfural (HMF) is typically involved, it is fundamentally significant to understand the different catalytic processes for HMFOR. In this work, we identify direct and synergistic oxidation types for HMFOR on cobalt oxide catalysts. For the direct HMFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 42 publications
4
74
0
Order By: Relevance
“…This peak is related to the nonhomogeneous charge contribution caused by the reaction between OH* and glycerol, which slowly shifts to a higher frequency and lower phase degree with raised potentials, as the white arrow shown in Figure B. From 1.30 V vs RHE, the peaks are located at the middle-frequency region (10 0 to 10 2 Hz), assigned with Co Td 2+ oxidation accompanied by OH* generation, according to Wang’s and Liu’s reports. , The generated OH* species can serve as active species to attack on the nucleophilic substrate, namely, glycerol, via direct oxidation. , …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This peak is related to the nonhomogeneous charge contribution caused by the reaction between OH* and glycerol, which slowly shifts to a higher frequency and lower phase degree with raised potentials, as the white arrow shown in Figure B. From 1.30 V vs RHE, the peaks are located at the middle-frequency region (10 0 to 10 2 Hz), assigned with Co Td 2+ oxidation accompanied by OH* generation, according to Wang’s and Liu’s reports. , The generated OH* species can serve as active species to attack on the nucleophilic substrate, namely, glycerol, via direct oxidation. , …”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that nucleophilic substrates could also be oxidized through the chemical reaction with (oxy)­hydroxides such as cobalt oxyhydroxide (CoOOH) via an indirect oxidation mechanism. , To rule out the possibility that Co 3 O 4 and Bi-Co 3 O 4 may reconstruct to (oxy)­hydroxides during Co Td 2+ oxidation, in situRaman spectroscopies were performed. In the OER, a peak at ∼560 cm –1 was observed, attributed to the formation of CoOOH (Figures S35A and S36A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations